The paddy grows in silence - Ingo Greve (Intereconomics, 1974)
In the attempt to build a South East Asian Community, similar experiences will be made as in other cases of merging disparate organisations. There are common interests, but also antagonisms, and a complicated network of interdependence will create a completely novel organism whose character cannot be foretold.
Keywords: 330; Asean